Synthesis and Optoelectronic Properties of Nonpolar Polyrotaxane Insulated Molecular Wires with High Solubility in Organic Solvents - Frampton, M; Sforazzini, G; Brovelli, S; Latini, G; Townsend, E; Williams, C; Charas, A; Zalewski, L; Kaka, N; Sirish, M; Parrott, L; Wilson, J; et al. (2008)
Hydrophilic polyanionic conjugated polyrotaxanes are readily synthesized in water by Suzuki coupling, but their high polarity and ionic nature limit the potential applications of these materials. Here, we demonstrate three methods for transforming these polar polyelectrolytes into nonpolar lipophilic insulated molecular wires. A water-soluble polyfluorene-alt-biphenylene β-cyclodextrin (CD) polyrotaxane was converted into nonpolar derivatives by methylation of the carboxylic acid groups with diazomethane and conversion of the hydroxyl groups of the CDs to benzyl ethers, trihexylsilyl ethers, benzoyl esters, and butanoate esters to yield polyrotaxanes that are soluble in organic solvents such as chloroform and cyclohexane. Elemental analysis, NMR spectroscopy, and gel permeation chromatography (GPC) data support the proposed structures of the organic-soluble polyrotaxanes. The extents of reaction of the polyrotaxane CD hydroxyl groups were 55% for trihexylsilyl chloride/ imidazole; 81% for benzyl chloride/sodium hydride; 72% for benzoyl chloride/pyridine/4- dimethylaminopyridine; and 98% butanoic anhydride/pyridine/4- dimethylaminopyridine. Alkylation, silylation, and esterification increase the bulk of the encapsulating sheath, preventing interstrand aggregation, increasing the photoluminescence efficiency in the solid state and simplifying the time-resolved fluorescence decay. The organic-soluble polyrotaxanes were processed into polymer light-emitting diodes (PLEDs) from solution in nonpolar organic solvents, thereby excluding ionic impurities from the active layer. © 2008 WILEY-VCH Verlag GmbH and Co. KGaA.